Industrial Upscaling of Electrospinning and Applications of Polymer Nanofibers: A Review. Issue 5 (8th January 2013) - Persano, Luana; Camposeo, Andrea; Tekmen, Cagri; Pisignano, Dario; Kim, Il‐Doo
Abstract Electrospun nanofibers are extensively studied and their potential applications are largely demonstrated. Today, electrospinning equipment and technological solutions, and electrospun materials are rapidly moving to commercialization. Dedicated companies supply laboratory and industrial‐scale components and apparatus for electrospinning, and others commercialize electrospun products. This paper focuses on relevant technological approaches developed by research, which show perspectives for scaling‐up and for fulfilling requirements of industrial production in terms of throughput, accuracy, and functionality of the realized nanofibers. A critical analysis is provided about technological weakness and strength points in combination with expected challenges from the market. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>